Tracing the methane cycle with lipid biomarkers in Lake Rotsee (Switzerland) - Naeher, Sebastian; Niemann, H.; Peterse, F.; Smittenberg, R.; Zigah, P.; Schubert, C. (Pergamon, 2014)
We analysed the distributions of glycerol dialkyl glycerol tetraethers (GDGTs) and other lipid biomarkers [glycerol dialkyl diethers (DGDs), fatty acids (FAs), sterols, hopanoids and phytol] in the water column and sediments of Lake Rotsee (Switzerland) to understand the processes and organisms involved in CH4 cycling. In the sediment we found substantial amounts of GDGT-0. This originates mainly from acetoclastic methanogens, as indicated by microbial data, high GDGT-0/crenarchaeol ratio and δ13C signature of the isoprenoid alkyl chains (ca. −35‰ to −30‰). The more depleted δ13C values of archaeol (as low as −62‰) can be attributed to hydrogenotrophic methanogens, with a potential contribution from methanotrophic archaea (anaerobic CH4 oxidising archaea). An increase in GDGT-0 in sediment layers deposited in the early 1920s [driven by an increase in organic matter supply to the sediment] indicates a maximum in methanogenic biomass and thus a potential peak in CH4 production, which fits with the eutrophication history of the lake. Excess methanogenesis most probably led to CH4 liberation to the water column and subsequent aerobic CH4 oxidation (MOx) as indicated by a higher concentration of diploptene and 17β,21β-homohopanoic acid, with δ13C values as low as −60‰ and −64‰, respectively.Variation in these markers in the sediment indicated changes in the abundance of aerobic CH4 oxidising bacteria (MOB), which thrive at the oxic/anoxic interface in the water column. In the water column, the presence of the C16:1ω8 FA indicated that the MOx community was dominated by Type I MOB. Incorporation of CH4-derived carbon into microbial biomass was also indicated by 13C-depleted diagnostic FAs with δ13C values as low as −53‰ (10-methyl-C16:0, C16:1ω7, C16:1ω5, C18:1ω7, C18:1ω5). In addition, CH4-derived carbon could also be traced into the biomass of photosynthetic organisms. In the water column, the sterols and phytol, originating from photosynthetic organisms, were 13C-depleted. This indicates significant CH4 turnover in the water column, leading to a 12C enrichment in the dissolved organic carbon (DIC)/CO2 pool, which was subsequently fixed by primary producers.